Directional tissue migration through a self-generated chemokine gradient - Donà, Erika; Khmelinskii, Anton; Knop, Michael (Nature, 2013)
The directed migration of cell collectives is a driving force of embryogenesis. The predominant view in the field is that cells in embryos navigate along pre-patterned chemoattractant gradients. One hypothetical way to free migrating collectives from the requirement of long-range gradients would be through the self-generation of local gradients that travel with them, a strategy that potentially allows self-determined directionality. However, a lack of tools for the visualization of endogenous guidance cues has prevented the demonstration of such self-generated gradients in vivo. Here we define the in vivo dynamics of one key guidance molecule, the chemokine Cxcl12a, by applying a fluorescent timer approach to measure ligand-triggered receptor turnover in living animals. Using the zebrafish lateral line primordium as a model, we show that migrating cell collectives can self-generate gradients of chemokine activity across their length via polarized receptor-mediated internalization. Finally, by engineering an external source of the atypical receptor Cxcr7 that moves with the primordium, we show that a self-generated gradient mechanism is sufficient to direct robust collective migration. This study thus provides, to our knowledge, the first in vivo proof for self-directed tissue migration through local shaping of an extracellular cue and provides a framework for investigating self-directed migration in many other contexts including cancer invasion.
Gesehen am 10.08.2017